A Closer Look on Student-Teachers’ Attitudes, Habits, and Their Comprehension Achievement toward Reading of Tertiary Level - Sartika, Eka (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
This study was aimed to find out (a) the existing phenomena of students’ reading attitudes, habit, and comprehension achievement, (b) whether or not there was significant correlation among the students’ reading attitudes, reading habits and their reading comprehension achievement, (c) whether or not there was contribution of students’ reading attitudes, reading habit and their reading comprehension achievement, (d) which variable gives the most contribution to the students’ reading comprehension achievement. The data were collected by distributing reading attitude and reading habit questionnaire and testing a reading comprehension for 313 students. The data were analyzed by Percentage analysis, Pearson Product Moment and Regression. The result showed that 1.6% students had very positive reading attitude, 95.9% students had positive reading attitude, 2.5% students had negative reading attitude. In reading habit, 23.1% students had very good reading habit, 72.3% students had good reading habit, and 4.6% students had average reading habit. There was a significant correlation between students’ reading attitude to their reading habit (.365 with sig .000). Significant correlation between either students’ reading attitude or reading habit and their reading comprehension achievement was not found. Based on their semester level, only the eighth semester students’ reading attitudes insignificantly correlate to their reading habits (.134 with sig .233). Meanwhile, only the fourth semester students’ reading attitudes correlate to their reading comprehension achievement (.290 with sig .011). In general, students’ reading attitudes contributed 13.3% to their reading habit. Finally 8.6% of the fourth semester students’ reading comprehension achievement was influenced by the combination of reading attitudes and reading habits.